THE IDENTITY CRISIS OF LANGUAGE AMONG URBAN TEENAGERS: A SOCIOLINGUISTIC STUDY ON THE SHIFT OF MOTHER TONGUE - NAFISAH HIDAYAH (JETA (Journal of English Teaching and Applied Linguistic), 2025)
Please The phenomenon of mother tongue shift among urban youth has emerged as an increasingly prominent issue amid the tides of globalization and digitalization. A language that should serve as a symbol of cultural identity is now experiencing a decline in both usage and meaning in the daily lives of the younger generation, particularly in urban areas. This article aims to examine in depth the factors contributing to the shift of the mother tongue and its implications for the linguistic identity of urban Indonesian youth. Using a qualitative-descriptive approach and library research methods, this study synthesizes findings from various scholarly journals and academic books related to sociolinguistics, psycholinguistics, and language behavior among youth. The results indicate that this shift is driven by the dominance of slang, the influence of social media, formal education systems that inadequately support the preservation of the mother tongue, and the weakening role of families in language transmission. As a result, youth are experiencing a linguistic identity crisis, reflected in a diminished sense of pride in their mother tongue and reduced communicative ability with older generations. This article highlights the need for synergy between educational institutions, families, and government policies to address this phenomenon and restore the mother tongue as a vital component of national identity